CONSTRUCTION OF TORSIONAL VIBRATION MECHANICS MODEL OF SCRAPER CONVEYOR AND ANALYSIS OF WORKING CONDITIONS THROUGH BENDING SECTION - MAO Jun; ZHANG YunSheng; XIE ChunXue; LIU ZhiXiang; XIE Miao (Jixie qiangdu)
This article is a study on the physical properties of the scraper under torsion. At first, the process of the scraper conveyor passing through the curved section of the conveyor is analyzed, and then on this basis, the bending moment and the additional resistance of the curved section are analyzed with the aid of a computer based on the dynamic model. Introduce the Voigt elastic viscosity model as a processing method, establish the model, and then use MATLAB programming to realize the pre-processing of the analysis. Finally, through data simulation, the characteristic data of the system（torsion, vibration, speed, etc.） under different material loading conditions at different positions of the scraper through the bending section are obtained. The analysis results show that when the scraper passes through the bending section, the system will produce a certain torsional vibration; for the presence or absence of materials, the scraper can be regarded as being in the load and no-load stages. The torsional vibration intensity is more pronounced under no-load conditions than when the front and rear are loaded; for the entire scraper, when it passes through the bending section, the closer the scraper chain system（swing, vibration, Speed, etc.） the more significant the feature changes.